BUREAUCRACY REFORM THROUGH THE PERSPECTIVE OF PUBLIC ADMINISTRATION IN INDONESIA - Ishak, Deding (LPPM STIE Muhammadiah Bandung, 2021)
Political developments in the new order era in Indonesia were filled with collusion, corruption and nepotism (KKN), so this required bureaucratic reform. To find a comprehensive understanding of the importance of implementing public reform from the perspective of public administration, it is then necessary to look at how the model of bureaucratic reform has previously been carried out, both in Indonesia and in other countries. A qualitative approach is used in this research method with research data sources and previous studies. The study results indicate that there are two dimensions related to bureaucratic reform that occurred in various countries, namely the organizational dimension and the human resource dimension of the apparatus.